The psychosocial aid response after the 22/03/2016 attacks in Belgium: a community case study - Muysewinkel, Emilie; Vesentini, Lara; Van Deynse, Helena; Stene, Lise Eilin; Bilsen, Johan; Van Overmeire, Roel (Frontiers in Public Health, 2024)
Introduction After the terrorist attacks, early psychosocial care is provided to people considered at risk of developing mental health issues due to the attacks. Despite the clear importance of such early intervention, there is very few data on how this is registered, who is targeted, and whether target-recipients accept such aid. Methods Using registry data from the Centre General Wellbeingwork (CAW), a collection of centers in the regions Brussels and Flanders that provide psychosocial care, we examined the early psychosocial care response after the terrorist attacks of 22/03/2016 in Belgium. Results In total, 327 people were listed to be contacted by the CAW, while only 205 were reached out to (62.7%). Most were contacted within a month (84.9%), and were victims of the attacks (69.8%). Overall, the majority was female (55.6%). Conclusion Overall, target recipients were witnesses and survivors of the attacks, though a large proportion of people were not reached by the early outreach.